Motivation among Hospital volunteers: an empirical analysis in Portugal - Ferreira, Marisa R. (2013)
The purpose of this paper is to identify the different types of motivations in hospital volunteers. We present a literature review about different types of motivation and we collect data from hospital volunteers through a questionnaire. Four different motivation categories are identified: development and learning, altruism, career recognition and belonging and protection. The main motivations expressed are development and learning, followed by altruism. Belonging and protection, followed by career recognition are the least cited motivations. Career recognition is negatively correlated with age, and belonging/ protection is negatively correlated with education. That is, younger volunteers present more career recognition motives and less educated volunteers have more from protection and belonging. This study encompasses hospital volunteers and their motivations. The paper is useful to policy makers aiming to develop targeted approaches to attracting and retaining volunteers.